2019
DOI: 10.1111/jgh.14917
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative evidence for the relationship between body mass index and the risk of esophageal cancer: An updated meta‐analysis with evidence from 25 observational studies

Abstract: Background and Aim:A large number of papers reporting the relationships between body mass index (BMI) and esophageal cancer (EC) risk have been published in the past few decades; however, these results are inconsistent. Therefore, we carried out meta-analyses to explore the relationships between BMI and the risk of EC (including esophageal squamous cell carcinoma [ESCC] and esophageal adenocarcinoma [EADC]). Methods: We used the Web of Science, PubMed, and Embase to identify all published/online articles befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Considering that obesity also increases the risk of gastroesophageal reflux disease and BE, the obesity epidemic is closely associated with the increased incidence of esophageal adenocarcinoma globally [2,[56][57][58]. A meta-analysis from 25 epidemiological studies revealed that obesity increased the risk of EC, particularly esophageal adenocarcinoma [59]. There is a strong positive relationship between higher BMI and the risk of esophageal adenocarcinoma [60,61].…”
Section: Sex Differences In Esophageal Cancer Incidencementioning
confidence: 99%
“…Considering that obesity also increases the risk of gastroesophageal reflux disease and BE, the obesity epidemic is closely associated with the increased incidence of esophageal adenocarcinoma globally [2,[56][57][58]. A meta-analysis from 25 epidemiological studies revealed that obesity increased the risk of EC, particularly esophageal adenocarcinoma [59]. There is a strong positive relationship between higher BMI and the risk of esophageal adenocarcinoma [60,61].…”
Section: Sex Differences In Esophageal Cancer Incidencementioning
confidence: 99%
“…Weight and height did not show statistically signi cance association with EC in our study. A metaanalysis study showed high risk of obesity with EAC but inverse association to ESCC (33). Another study in Netherland also showed signi cant association between obesity and overweight with EC (34).…”
Section: Discussionmentioning
confidence: 95%
“…While no signi cant association was found between overweight and esophageal cancer (RR: 1.14, 95%CI: 0.98-1.30). However, it's interesting that both overweight and obesity could increase risk of esophageal adenocarcinoma and decrease risk of esophageal squamous cell carcinoma according to subgroup analysis (22). Compared with normal weight, overweight and obesity were demonstrated to be related with a 4% (OR: 1.04, 95%CI: 0.96-1.12) and 13% (OR: 1.13, 95%CI: 1.03-1.24) increased risk of gastric cancer respectively.…”
Section: Association Between Bmi and Various Cancer Riskmentioning
confidence: 99%